Voluntary Earnings Notifications and Post‐earnings‐announcement Drift. (22nd September 2021) - Nam, Giman; Choi, Sunhwa
Abstract: We examine whether voluntary disclosure of earnings notifications mitigates the post‐earnings‐announcement drift (PEAD). An earnings notification, which is a firm's voluntary announcement of the date of its earnings announcement (EA), increases investor attention to firms' upcoming EAs and thus facilitates the incorporation of earnings news into stock prices. We find that firms with earnings notifications experience less PEAD and that the effect of earnings notifications on PEAD is greater for less visible firms. The results highlight the role of earnings notifications in improving price efficiency with respect to earnings news.